Despite increasing aldosterone, elevated potassium is not necessary for activating aldosterone‐sensitive HSD2 neurons or sodium appetite - Fazan, Frederico S. (Physiol Rep, 2021)
Restricting dietary sodium promotes sodium appetite in rats. Prolonged sodium restriction increases plasma potassium (pK), and elevated pK is largely responsible for a concurrent increase in aldosterone, which helps promote sodium appetite. In addition to increasing aldosterone, we hypothesized that elevated potassium directly influences the brain to promote sodium appetite. To test this, we restricted dietary potassium in sodium‐deprived rats. Potassium restriction reduced pK and blunted the increase in aldosterone caused by sodium deprivation, but did not prevent sodium appetite or the activation of aldosterone‐sensitive HSD2 neurons. Conversely, supplementing potassium in sodium‐deprived rats increased pK and aldosterone, but did not increase sodium appetite or the activation of HSD2 neurons relative to potassium restriction. Supplementing potassium without sodium deprivation did not significantly increase aldosterone and HSD2 neuronal activation and only modestly increased saline intake. Overall, restricting dietary sodium activated the HSD2 neurons and promoted sodium appetite across a wide range of pK and aldosterone, and saline consumption inactivated the HSD2 neurons despite persistent hyperaldosteronism. In conclusion, elevated potassium is important for increasing aldosterone, but it is neither necessary nor sufficient for activating HSD2 neurons and increasing sodium appetite.